(E)-4-Methoxy-N00-(2,4,5-trimethoxybenzylidene) benzohydrazide hemihydrate - Chantrapromma, Suchada; Boonnak, Nawong; Horkaew, Jirapa; Ching, Kheng Quah; Fun, Hoong Kun (International Union of Crystallography, 2014)
The title compound crystallizes as a hemihydrate, C18H20N2O50.5H2O. The molecule exists in an E conformation with respect to the C N imine bond. The 4-methoxyphenyl unit is disordered over two sets of sites with a refined occupancy ratio of 0.54 (2):0.46 (2). The dihedral angles between the benzene rings are 29.20 (9) and 26.59 (9), respectively, for the major and minor components of the 4- methoxy-substituted ring. All methoxy substituents lie close to the plane of the attached benzene rings [the Cmethyl—O—C— C torsion angles range from 4.0 (12) to 3.9 (2)]. In the crystal, the components are linked into chains propagating along [001] via N—H O and O—H O hydrogen bonds and weak C—H O interactions.